2017
DOI: 10.5120/ijca2017915778
|View full text |Cite
|
Sign up to set email alerts
|

Techniques used for Bone Density Measurement

Abstract: The objective of this paper is to propose the methodology which determines the density of human bones. Osteoporosis is a common disease related to human bone metabolism and is defined as the "diseases characterized by low bone mass and micro architectural deterioration of bone tissue leading to enhance bone fragility and consequent increase in fracture risk". This paper gives the comparative study of the methods used to measure bone mineral density.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…Many studies indicated that a heel ultrasound is used to assess bone structure and strength and is used worldwide for osteoporotic fracture risk assessment when DXA the gold standard tool in diagnosis is not available, although it is not to be used as a diagnostic tool (ISCD, 2013;Quiros Roldan et al, 2017). The positive attributes of the heel ultrasound test are that it involves no risks or harm and is a cost-effective, comfortable, pain-free, and radiation-free test that is easy to use and only takes a few minutes to perform (Shewale et al, 2017;Komar et al, 2019). Studies have shown the quantitative ultrasound densitometry technique to be useful in assessing skeletal health status changes due to exercise in all age groups and as a research tool (GE Medical Systems Lunar, 2010;Babatunde and Forsyth, 2013;Yesil et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Many studies indicated that a heel ultrasound is used to assess bone structure and strength and is used worldwide for osteoporotic fracture risk assessment when DXA the gold standard tool in diagnosis is not available, although it is not to be used as a diagnostic tool (ISCD, 2013;Quiros Roldan et al, 2017). The positive attributes of the heel ultrasound test are that it involves no risks or harm and is a cost-effective, comfortable, pain-free, and radiation-free test that is easy to use and only takes a few minutes to perform (Shewale et al, 2017;Komar et al, 2019). Studies have shown the quantitative ultrasound densitometry technique to be useful in assessing skeletal health status changes due to exercise in all age groups and as a research tool (GE Medical Systems Lunar, 2010;Babatunde and Forsyth, 2013;Yesil et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is the tissue-level properties in combination with the bone geometry that determine fracture risk. The most widely applied technique to measure bone mineral density is the dual energy x-ray absorptiometry (47).…”
Section: Skeletal Capacitymentioning
confidence: 99%
“…Many studies indicated that heel ultrasound is used to assess bone structure and strength and is used worldwide for osteoporotic fracture risk assessment when DXA, the gold standard tool in diagnosis, is not available, although it is not to be used as a diagnostic tool (Fitzgerald et al, 2020;ISCD, 2013;Quiros Roldan et al, 2017). The positive attributes of the heel ultrasound test are that it involves no risks or harm, and is a cost-effective, comfortable, pain-free, radiation-free test that is easy to use and only takes a few minutes to perform (Komar et al, 2019;Shewale et al, 2017). Studies have shown the quantitative ultrasound densitometry technique to be useful in assessing skeletal health status changes due to exercise in all age groups and as a research tool GE Medical Systems Lunar, 2010;Yesil et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Although DXA is considered the best tool to diagnose osteoporosis, it uses ionising radiation and is expensive to use, requiring specialist equipment and personnel, and is not always globally accessible (Clynes et al, 2020). Other alternative imaging tools are available to estimate BMD (Shewale et al, 2017). These include high resolution peripheral quantitative computed tomography (pQCT) that uses ionisation radiation to assess bone density three dimensionally, with measurements of geometry and volumetric bone density taken in trabecular and cortical areas, which are prone to fractures (Di Iorgi et al, 2018).…”
Section: Measures Of Osteoporosis -Diagnosticsmentioning
confidence: 99%
See 1 more Smart Citation